1 - Sciences sociales et développement - AKE, Claude (Africa Development, 1980)
* Une première version anglaise, disponible sur demande, a été publiée par le CODESRIA sous forme de Publication Occasionnelle. In this article the writer looks at the relationship between social sciences and development in Africa with the view of suggesting the ways which social sciences could be more useful to the development process in Africa. His first two paragraphs analyse the problem of development itself and the nature of social science knowledge. He points out that «conceptions of development could lead to misdirection of energy, waste national resources and the weakening of the sense of national purposeTherefore one of the major contributions of social science is to try and provide an adequate conception of development. But if social science to look critically at the conception of development, it must also look criti cally at itself. Although efforts have been made at various conferences and seminars to describe the nature of the prevailing social science, and the general relationship of social science to development, the new directions of the social sciences which are to be created are not yet clearly mapped out. In the rest of the article, the author comments briefly on the condi tions of the growth of social science in Africa on such aspects as manpower, research facilities, the political context and the utilization of social science knowledge, etc ... The study of the manpower resources in social science is certainly one of the first task to achieve concerning the problem of manpower. It should begin with a careful inventory of African Social Scientists. Hower ver, since the critical problem for Africa is the production of a social science which is more appropriate for Africa's development needs, the quality African Social Scientists will thus become a critical aspect. A most impor tant step towards this would be a detailed analysis of the content of social science curricula especially in institutions of higher learning in Africa. As for research facilities, more detailed and systematic work on a comparative basis for the whole of Africa is of the highest priority. One useful approach would be to compare the effects of the funding and conducting research in universities, private organizations and government establishments. It is also important to investigate the political situation as it influen ces the production, distribution and use of social science, because social science, like any other science cannot be isolated from the contradictions of the social context. In any case, the type of social science prevailing Africa may not be all it ought to be but it is all it can be in the sense that it reflects the interests of the ruling classes in Africa and the realities of the economic dependence of Africa on the West. The last condition for the growth of social science in Africa is the problem of the utilization of social science knowledge. Although it does not seem to be conspicuous to researchers, the production of science in neral and social science in particular cannot be separated from its utilization. But since the problem of utilization is not clear in itself, the first task set African Social Scientists is to clarify it by determining who uses social science knowledge, how and why. The author concludes by suggesting that since scholarly effort has to be made simultaneously on several fronts, what appears to be needed not several research programmes but one comprehensive research programme. Claude AKE, Doyen de la Faculté des Sciences Sociales, Université de Port Harcourt, Nigéria.